2009
DOI: 10.1007/s11002-009-9097-y
|View full text |Cite
|
Sign up to set email alerts
|

Guilty by stereotypic association: Country animosity and brand prejudice and discrimination

Abstract: This research tests the proposition that brands suffer prejudice and discrimination due to animosity toward a country with which they have a strong stereotypic association. In the first study, attitudinal data collected across a range of brands that vary in terms of the strength of the brand–country association indicate that brands with strong stereotypic association with a country suffer direct prejudice, in the form of more negative attitudes, related to animosity. When the brand–country association is less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 30 publications
(53 reference statements)
0
51
1
2
Order By: Relevance
“…In the original animosity model (Klein et al, 1998), consumer judgments and attitudes were not examined, although other studies empirically proved that animosity influences consumers' evaluative responses (Russell & Russell, 2010). Shoham et al (2006), in assessing Israeli Jewish consumers' opinion about Israeli-Arab products, found that animosity equally impacted product quality judgments and willingness to buy.…”
Section: Perceived Animositymentioning
confidence: 99%
“…In the original animosity model (Klein et al, 1998), consumer judgments and attitudes were not examined, although other studies empirically proved that animosity influences consumers' evaluative responses (Russell & Russell, 2010). Shoham et al (2006), in assessing Israeli Jewish consumers' opinion about Israeli-Arab products, found that animosity equally impacted product quality judgments and willingness to buy.…”
Section: Perceived Animositymentioning
confidence: 99%
“…Funk et al's (2010) study assessed US consumers willingness to purchase a hybrid foreign product using Toyota as an example. Russell and Russell's (2010) study tested how the strength of the brand-country stereotypic association influenced the relationship between animosity and US consumers' responses to the brand. Our research extends this stream of animosity research to the sponsorship context and explores how animosity toward a country impacts upon attitudes toward the sponsors originating from that country.…”
Section: Economic Animositymentioning
confidence: 99%
“…The observed level of prejudice and discrimination against the brands depend on the strength of the brand-country association (Russell & Russell, 2010). Rose, Rose, & Shoham (2009) found animosity levels differed strongly between cultural subgroups in Israel, and they suggest that this highlights the importance of considering such cultural subgroups when studying animosity.…”
Section: Introductionmentioning
confidence: 99%
“…Animosity may negatively impact trust in a supplier (Jimenez & Martin, 2010), acceptance or rejection of symbols in mass communication ( Lwin, Stanaland & Williams, 2010), and evaluations of brands that are associated with the animosity target (Russell & Russell, 2010).…”
Section: Introductionmentioning
confidence: 99%